2007
DOI: 10.1086/514821
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Factor H–Binding Protein Variants and NadA among Meningococcal Group B Isolates from the United States: Implications for the Development of a Multicomponent Group B Vaccine

Abstract: Susceptibility to bactericidal activity can be predicted, in part, on the basis of fHBP phenotypes. Both vaccines have the potential to prevent most group B disease in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 40 publications
2
62
1
Order By: Relevance
“…Even the hyperinvasive ST32 complex, which is dominated by one subfamily B variant (B24, variant 1.1), contains at least 27 additional fHBP sequence variants (29). These results were also seen in other smaller, non-prevalence-based studies for MnB and in other N. meningitidis serogroups (32,112,113). Hao et al recently conducted a comparative analysis of 38 Neisseria genomes and found that MLST could not predict virulence gene content or strain phenotype (114).…”
Section: Heterogeneity Of Fhbp Variants Expressed With Common N Menimentioning
confidence: 98%
See 1 more Smart Citation
“…Even the hyperinvasive ST32 complex, which is dominated by one subfamily B variant (B24, variant 1.1), contains at least 27 additional fHBP sequence variants (29). These results were also seen in other smaller, non-prevalence-based studies for MnB and in other N. meningitidis serogroups (32,112,113). Hao et al recently conducted a comparative analysis of 38 Neisseria genomes and found that MLST could not predict virulence gene content or strain phenotype (114).…”
Section: Heterogeneity Of Fhbp Variants Expressed With Common N Menimentioning
confidence: 98%
“…No SBA killing against the subfamily B isolate was observed using the subfamily A serum; however, some cross-protection was observed for the subfamily B vaccines and the subfamily A strains. Coverage studies for the nonlipidated variants have been further expanded and have demonstrated that as with lipidated proteins, SBA protection is subfamily specific; however, the breadth of coverage within the subfamily is not sufficiently covered when a single nonlipidated variant is used in the vaccine (20,31,113,118).…”
Section: Preclinical Evaluation Of the Potential Breadth Of Coverage mentioning
confidence: 99%
“…However, it was not seen to contribute to SBA against other heterologous strains producing fHbp subvariants ID 14 (NZ98/254), ID 15 (M01 240101) or ID 4 (M01 242922), in contrast to the cross-reactive response seen in preclinical studies. 48,57 Expression levels of fHbp have been shown to dramatically affect SBA responses 43,57,58 but all except one of the test strains were shown to bind a murine antibody against this antigen. 33 The NadA component of the vaccine induced high levels of SBA against indicator strain 5/99 in agreement with preclinical data.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…However, some isolates are resistant to vaccine-induced SBA probably due to genetic variability of the antigen and/or low expression of the protein. 24 This vaccine is currently being evaluated in a Phase 1/2 trial.…”
Section: Other Protein-based Vaccinesmentioning
confidence: 99%